Two-port network representations of D. C. electro-mechanical transducers - Paul, R. J. A. (College of Aeronautics, 1962)
Two port network representations are derived for the general linear magnetic and electric field transducers. The constraints imposed by linearity requirements are discussed. It is shown that for the most general form of transducer. the conversion of energy leads to non-linear relationships, and a method of solving these equations is suggested. Typical applications are included to illustrate the analysis procedure and in particular the case of the d. c. motor is discussed in detail.